Pueraria thomsonii Benth.: a high-biomass plant for cadmium phytoremediation with high accumulation in stems - Li, Xing; Luo, Xiaqin; Zhang, Yusheng; Zhou, Lijun; Wu, Lin; Wang, Binqiang; He, Shaolang; Huang, Shangshu; Sun, Yongming; Lv, Weisheng; Lin, Xiaobing (Frontiers in Plant Science, 2025)
Heavy metal contamination in farmland soils threatens food security and human health. Phytoremediation provides a sustainable strategy, with Pueraria thomsonii emerging as a promising candidate due to its high-biomass production. However, its metal accumulation dynamics remain uncharacterized. Therefore, a 3-year field experiment was conducted to investigate biomass production, the accumulation of heavy metals (Cd, Cr, As, and Pb) across growth stages, and the bioconcentration factor (BCF), translocation factor (TF), and removal rate in P. thomsonii. Results showed that P. thomsonii produced a total biomass of 10.81–21.22 t ha−1, accumulating 76.95–170.61 (Cd), 30.80–43.28 (Cr), 7.12–9.09 (As), and 18.16–39.30 (Pb) g ha−1 during 2020–2022. Stem Cd accumulation exceeded root tubers and leaves by 45%–205% at maturity, while leaf Cr, As, and Pb accumulation was higher than root tubers and stems by 149%–868%. Cd-BCF values >1 in stems and leaves indicated efficient bioaccumulation, contrasting with Cr-, As-, and Pb-BCF <1. Stem and leaf TF values of Cd, Cr, As, and Pb consistently exceeded >1 except for stem Cr TF in 2022. On average, in the 3-year experimental period, the removal rate of Cd surpassed Cr, As, and Pb by 94%–95%. Soil properties (organic matter, available N) significantly influenced BCF, while available N modulated TF. These findings suggest that the combination of high-biomass production and elevated Cd accumulation in stems positions P. thomsonii as a promising candidate for high-biomass phytoremediation of Cd-contaminated farmland soils.